Estudio retrospectivo de supervivencia y complicaciones de prótesis híbridas en pacientes edéntulos totales realizados en la Clínica Dental Docente de la Universidad Peruana Cayetano Heredia del año 2013 al 2016 - Araujo Guevara, Karen Gabriela (2020)
Hybrid prostheses in total edentulous patients have improved their quality of life, so it is essential to know survival and possible complications, to offer reliable treatment. Objectives: to evaluate and record the survival and complications of hybrid prostheses in total edentulous CDD-UPCH patients. Materials and methods: The study was descriptive, observational, retrospective, cross-sectional. Medical records of 37 patients (45 prostheses) installed from 2013 to 2016 were reviewed, data were recorded in Microsoft®Excel2016 and exported to the StataV15 statistical program. A univariate percentage analysis was used for the survival rate and biomechanical complications, and chi2 or Fisher's exact for the association with variables. Results: Survival (years) was higher: female sex, young patients, installed in upper arches, with early loading and having natural teeth as the antagonist. The most frequent biomechanical complications were: mucositis; being the same in both sexs and arches, with greater results in the older adult and conventionally loaded prostheses that have mixed prostheses as antagonists; and screw loosening was greater in female patients, older adults with conventionally loaded prostheses and with mixed prostheses as antagonists, without significant differences according to the type of arch. Conclusions: 5-year survival was 84.91% and failure 15.09%. The most frequent biomechanical complications were mucositis and screw loosening, and no associations of survival and biomechanical complications were found with; sex, age group, type of antagonist, compromised arch and type of load. Key words: survival, postoperative complications, prostheses, dental implants, mouth edentulous.